PENGARUH KOMUNIKASI ORGANISASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN BAGIAN NO SEW PADA PT ADIS DIMENSION FOOTWEAR KABUPATEN TANGERANG - Ahmad Khumaidi; Khaerul Fahmi; Temmy Setiawan (MANTRA (Jurnal Manajemen Strategis), 2026)
The Influence of Organisational Communication and Work Discipline on Employee Productivity in the No-Sew Department at PT Adis Dimension Footwear, Tangerang Regency. This study examines the partial and simultaneous effects of organisational communication and work discipline on employee productivity. Using a quantitative descriptive method with 70 respondents, the results show that both variables have significant effects on employee productivity.